Development of Physics E-Books Assisted by Flipbook and Augmented Reality (AR) to Increase Learning Motivation of High School Students - Kartika, Hera Anis; Purwanto, Andik; Risdianto, Eko (Asian Journal of Science Education, 2024)
The initial observation results indicate that students are less active in the learning process and easily give up when faced with tasks deemed difficult. This study aims to describe the feasibility of physics e-books aided by flipbooks and augmented reality (AR), describe students' responses and describe students' learning motivation after the implementation of physics e-books aided by flipbooks and augmented reality (AR). This research is a type of development research using the ADDIE model. Sampling was done using purposive sampling techniques consisting of students from the Eleventh-grade science 3 class at Public High School 7 in Kota Bengkulu. The instruments used were observation sheets, teacher interview sheets, validation sheets, student response questionnaires, and pretest and posttest student learning motivation questionnaires, with data collection techniques including interviews, questionnaires, and documentation. Data were analyzed using quantitative data analysis. The research results show that the feasibility test criteria for physics e-books were obtained with a very good category. Students also responded very well to the developed physics e-books. Based on the analysis of student learning motivation questionnaires using the Gain value, it was found that students experienced an increase in learning motivation after using the developed physics e-books. Therefore, it can be concluded that physics e-books aided by flipbooks and augmented reality (AR) are highly suitable for use as learning media and can enhance students' learning motivation, especially in dynamic fluid materials